Line Evolution of the Nova V5587 Sgr from Early to Nebula Phase - T. Kajikawa; A. Arai; M. Nagashima; H. Kawakita; M. Yamanaka; K. Kawabata; S. Kiyota (Acta Polytechnica CTU Proceedings, 2015)
The spectral evolution of the nova V5587 Sgr has been monitored at Koyama Astronomical Observatory and Higashi-Hiroshima Observatory, Japan, from the early to nebula phase. The nova rebrightened several times. The spectra during the early phase showed emission lines of H α, H β, O I, He I, He II, N II, Fe II. Nova V5587 Sgr is classified into the Fe II type. The helium abundance of the nova is estimated as N(He)/N(H) = 0.134 ± 0.09. The light curve, the spectral evolution, and the helium abundance in V5587 Sgr are similar to those of the nova PW Vul.